A novel pilot‐scale tubular bioreactor‐enhanced floating treatment wetland for efficient in situ nitrogen removal from urban landscape water: Long‐term performance and microbial mechanisms. (2nd June 2019) - Cui, He; Yang, Yinchuan; Ding, Yu; Li, Dan; Zhen, Guangyin; Lu, Xueqin; Huang, Minsheng; Huang, Xiao
Abstract: In order to strengthen in situ nitrogen removal of urban landscape water, a novel pilot‐scale tubular bioreactor‐enhanced floating treatment wetland (TB‐EFTW) was constructed, and the long‐term performance and responsible microbial mechanisms were investigated in this study. The results showed that the system could remove 81.5% nitrogen from the landscape water after 240 days' operation. Moreover, the contribution rate of plant absorption to nitrogen was low (8.3%), which indicated that microbial biotransformation rather than plant absorption played a more key role in nitrogen removal in TB‐EFTW system. The declining dissolved oxygen (DO) concentration along the axial direction of tubular bioreactor (TB) resulted in the sequential bacterial community of nitrifying, aerobic denitrifying, and anoxic denitrifying bacteria in the front, middle, and final part of TB. High‐throughput sequencing results demonstrated that the internal environment of the system realized the coexistence of nitrifying, aerobic denitrifying and anoxic denitrifying process. The reason was mainly because that oxic‐anoxic (O‐A) areas were formed in sequence along the axial direction of tubular bioreactor. Overall, a unique advantage in nitrogen removal was achieved in TB‐EFTW, which could provide important references for in situ treatment of urban landscape water. Practitioner points: TB‐EFTW strengthened nitrogen removal for in situ urban landscape water treatment. Microbial conversion played a key role in nitrogen removal of the TB‐EFTW system. The unique distribution of oxic‐anoxic (O‐A) areas was formed in sequence along the TB. Nitrification, aerobic, and anoxic denitrification were synergistically involved in the TB. Abstract : The excellent nitrogen removal performance was achieved in the tubular bioreactor‐enhanced floating treatment wetland (TB‐EFTW), which was mainly due to the unique distribution of oxic‐anoxic areas and the coexistence of 'nitrifier, aerobic‐denitrifier and anoxic‐denitrifier' along the TBs.